OPTIMALISASI PERAN PEMUDA DALAM PEMBANGUNAN EKONOMI KREATIF BERBASIS SEKTOR PARIWISATA - Ferry Siswadhi; Cyntia Carolina; Suci Marselina (LPPM - STIE SAKTI ALAM KERINCI, 2020)
Historical roles and involvement have placed youth as a strategic group with significant social transformation. Globalization and modernization give birth to cultural imitations among youth, by assuming they are more proud of the false identity or imitation culture they perceive in their daily lives. In the end, the identity of the locality is lost and threatened to lose its transformative character in the life of the nationThat is, the identity of nationalism and the pioneering character of youth is reexamined. Globalization should be a source of inspiration to make future changes. The free market era will create a form of injustice in the equity of the economy because the stronger will be stronger and the weaker will become weaker. In this condition, the creative economy can be used as one of the solutions in facing the competitive level, so that the level of competition is not only determined by how big process of production process level but also creativity aspect and innovation start to play a very important role besides technology factor provide a strong influence on the development of creative economy. Exploring the cultural richness and natural beauty of this country to be the choice of the nation's creative industry sector is expected to be extremely remarkable by combining the strength of local cultural values with the demands of global needs.